Dramaturgical interaction in virtual reality as a stage for self- presentation: A study on five content creators in Jakarta - Hany Ditania; Rusfadia Saktiyanti Jahja; Atik Kurniawati (C-DISC, 2025)
This study aims to identify the forms of self-presentation performed by content creators on Instagram through a dramaturgical approach, as well as to explain the role of followers in shaping the creators' identity presentation on social media. This research employs a qualitative approach with a case study method, conducted from January to August 2023. The subjects consist of five Instagram content creators aged 20–30 years, all based in Jakarta. Data was collected through observation, interviews, documentation, and literature study, and were further supported by expert insights in the field of social media. The data were analyzed using Erving Goffman's dramaturgical theory. The findings reveal that content creators construct their digital persona on the front stage through curated visual content, a consistent communication style, and narratives tailored to audience expectations. Meanwhile, aspects of private life and emotional fatigue are managed backstage as part of a more personal space. Followers play a role in shaping content creators’ identities through comments, direct messages, and interactions that foster one sided emotional connection. Identity on Instagram is not a pure reflection of the self but the result of personal strategy, algorithmic pressure, and the ongoing demand for social connectivity.